Writers-etnographers in the Russian literature of the 2nd half of the 19th century: artisans, popularisers, literary nomads?.. - Созина, Елена (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
The article examines the phenomenon of ethnographic fiction which emerged in the Russian culture in the 2nd half of the 19th century. The works of Vladimir Dal dating to the 1830s and 1840s mark the beginnings of this line of writing. The authors who contributed to the genre were little known figures, like Flegont Arseniev, Ioasaph Zheleznov, Konstantin Nosilov, Porfiry Infantiev, Aleksandr Kruglov and Sergei Maksimov, as well as established ones, including Fyodor Reshetnikov or Vladimir Korolenko, for whom this was not the exclusive form of literary expression. The specific character of their works entails representing various aspects of the life of the many nations of the Russian Empire, describing their places of residence, their occupations and trades. The texts by ethnography fiction writers were quite often fashioned after one model and rather schematic; yet they rose out of personal experience and proved important for expanding the worldview of the reading public in Russia.